Volterra’s theory of elastic dislocations for a transversally isotropic homogeneous hollow cylinder - Laserra, E.; Pecoraro, M. (Нелінійні коливання, 2003)
This work will consider Volterra’s theory of elastic dislocations in the case of a transversally isotropic homogeneous hyperelastic hollow cylinder. We obtain explicit equations for vector field of displacements, for tensor fields of strain and stress, and for forces upon the boundary. Розглянуто теорiю Вольтерри для пружних дислокацiй у випадку трансверсально iзотропних однорiдних надпружних порожнистих цилiндрiв. Одержано рiвняння для векторного поля перемiщень, тензорного поля напружень i сил на межi.